Comparison of nano encapsulated thyme essential oils on intestinal microbial population and anti-oxidation status of broilers - Ardabili, ME; Nobakht, A; Safamehr, A; Mehmannavaz, Y; Zanebure, A (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was conducted to evaluate the effects of non and nano-capsulated thyme essential oils with saturated and unsaturated lipids (tallow and canola oil) and two levels of diet crude protein (standard and low than standard) on intestinal microbial population and anti-oxidation status of broilers. In this study, 384 Ross-308 broiler chickens in a factorial engagement of 2×2×2 (2 medicinal plant essential oils, two sources of vegetable oils, and 2 levels of diet crude protein) were used in a completely randomized design with 8 treatments, 4 replicates, and 12 bird in each replicate for 42 days. Experimental periods included starter (1-10 days), grower (11-24 days), and finisher (25-42 days). Canola oil significantly reduced the intestinal coliforms population. In contrast, tallow increased them (P<0.05), a similar effect was observed with thyme forms, so the lowest coliform population blogged to the nano-capsulated form of thyme. In contrast, the highest coliform population resulted in non-capsulated thyme essential oil (P<0.05). In an interaction between thyme essential oil form and diet crude protein level, the lowest coliform population was observed with diet contained nano-capsulated thyme essential oil and low level of diet crude protein (P<0.05). Regarding antioxidant status, reducing the diet crude protein increased MDA and GPX (P<0.05). In an interaction between diet crude protein and thyme form, a diet with low crude protein and capsulated thyme increased the level of SOD (P<0.05). In general, results of the current experiment indicated that in Ross-308, broiler chickens using capsulated thyme essential oil with canola oil and low crude protein improves intestine microbial population and antioxidant status of broilers.